2021
DOI: 10.1016/j.jamda.2021.03.022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medication Reconciliation via a Patient Portal on Medication Discrepancies: A Randomized Noninferiority Study

Abstract: Background: Medication reconciliation has become standard care to prevent medication transfer errors. However, this process is time-consuming but could be more efficient when patients are engaged in medication reconciliation via a patient portal. Objectives: To explore whether medication reconciliation by the patient via a patient portal is noninferior to medication reconciliation by a pharmacy technician. Design (including intervention): Open randomized controlled noninferiority trial. Patients were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…Not surprisingly, we identified that the overall score of the PHR was higher for PHR users compared to PHR non‐users. Despite the small sample size, our score for the PHR rated by PHR users was comparable (8 versus 8.1) with the mean score of patient satisfaction of using a PHR for MR rated by PHR users ( n = 233) in the study of Ebbens et al 31 This may indicate that our study population is representative of the Dutch population.…”
Section: Discussionsupporting
confidence: 50%
“…Not surprisingly, we identified that the overall score of the PHR was higher for PHR users compared to PHR non‐users. Despite the small sample size, our score for the PHR rated by PHR users was comparable (8 versus 8.1) with the mean score of patient satisfaction of using a PHR for MR rated by PHR users ( n = 233) in the study of Ebbens et al 31 This may indicate that our study population is representative of the Dutch population.…”
Section: Discussionsupporting
confidence: 50%
“…This may have promoted patients’ overall favorable opinions of SMMRT, despite the barriers experienced when returning SMMRT via secure messaging. Recent literature reports that patients can identify medication discrepancies in their own personal health record with comparable accuracy to a pharmacy technician, supporting the assertion that patients can be closely involved in the medication reconciliation process [ 32 , 33 ], as they were in the SMMRT intervention. SMMRT has the potential to reduce the risk of ADEs and rehospitalizations by providing a mechanism for patients to help identify medication discrepancies.…”
Section: Discussionmentioning
confidence: 89%
“…Performing MR is a time-consuming process. 17 , 18 The patient interview of obtaining the BPMH as the crucial step takes 12 to 46 minutes per patient. 19 , 20 In the electronic medical record system (EMRs), all medical staff can review health records (eg, medication history, laboratory results, simple text reports of microbiology and pathology, or radiographic images) and receive medical assistance from prescription-audit systems, and clinical pharmacists can review lists of medications procured from ambulatory prescription, information stored in local EMRs, and computerized orders.…”
Section: Introductionmentioning
confidence: 99%